Shelf life improvement of traditional Intermediate Moisture (IM) mangoes by addition of humectant - Montes, Maria Clara I.
Shelf life of traditional intermediate moisture mangoes was extended by one and a half months at 20°C and 30°C through the addition of 15% glycerol. The aw lowering effect of glycerol caused a decrease in the rate of browning reactions during storage of dried mangoes. Based on the study, Maillard browning was the main chemical reaction causing deterioration and shortening the shelf life of dried mangoes. Storage stability of dried mangoes was studied s a function of storage temperature. The criteria for storage stability were based on non-enzymatic browning and ascorbic acid degradation. Results of kinetic studies suggested zero-order reaction for non-enzymatic browning, and first-order reaction for ascorbic acid degradation. Browning in dried mangoes was three times faster than 40°C than at 20°C and 30°C.